Synthesis and anticancer activity of novel water soluble benzimidazole carbamates - Cheong, Jae Eun; Zaffagni, Michela; Chung, Ivy; Xu, Yingjie; Wang, Yiqiang; Jernigan, Finith E.; Zetter, Bruce R.; Sun, Lijun (Elsevier, 2018)
Metastases account for more than 90% of all cancer deaths and respond poorly to most therapies. There remains an urgent need for new therapeutic modalities for the treatment of advanced metastatic cancers. The benzimidazole methylcarbamate drugs, commonly used as anti-helmitics, have been suggested to have anticancer activity, but progress has been stalled by their poor water solubility and poor suitability for systemic delivery to disseminated cancers. We synthesized and characterized the anticancer activity of novel benzimidazoles containing an oxetane or an amine group to enhance solubility. Among them, the novel oxetanyl substituted compound 18 demonstrated significant cytotoxicity toward a variety of cancer cell types including prostate, lung, and ovarian cancers with strong activity toward highly aggressive cancer lines (IC50: 0.9–3.8 μM). Compound 18 achieved aqueous solubility of 361 μM. In a mouse xenograft model of a highly metastatic human prostate cancer, compound 18 (30 mg/kg) significantly inhibited the growth of established tumors (T/C: 0.36) without noticeable toxicity.